Laboratory Monitoring or Measurement of Direct Oral Anticoagulants (DOACs): Advantages, Limitations and Future Challenges - Favaloro, Emmanuel J; Pasalic, Leonardo; Curnow, Jennifer; Lippi, Giuseppe (Current drug metabolism, 2017)
The Direct Oral Anticoagulants (DOACs) represent a new generation of antithrombotic agents, providing direct inhibition of either thrombin (factor IIa; FIIa) or activated factor X (FXa). Around the globe, their use is progressively rising, as these new agents replace the historical anticoagulants (heparin and vitamin K antagonists including warfarin) for various clinical conditions in medical practice. Other acronyms used to designate DOACs include TSOAC (target specific oral anticoagulants) and NOAC (novel; or non-vitamin K antagonist oral anticoagulants). Currently available DOACS include dabigatran (FIIa inhibitor), along with rivaroxaban, apixaban, edoxaban and betrixaban (FXa inhibitors). This narrative review aims to briefly summarise the evidence concerning utility of different laboratory assays for qualitative or quantitative assessment of DOACs, emphasizing the difference between 'drug monitoring' and 'drug measurement' and ultimately discussing advantages and limitations of these processes. Recently, the dogma that these innovative anticoagulant agents will not necessitate laboratory testing has been challenged with the recognition that assessment of drug concentration or activity may be required in some circumstances, although this does not immediately translate to the concept of 'drug monitoring'.